2021
DOI: 10.1530/erc-20-0106
|View full text |Cite
|
Sign up to set email alerts
|

Limited efficacy of lenvatinib in heavily pretreated anaplastic thyroid cancer: a French overview

Abstract: Anaplastic thyroid cancer (ATC) is a rare lethal disease. Lenvatinib is an off-label therapeutic option for ATC in most countries, except in Japan. The aim of this multicentre retrospective survey was to analyse the efficacy and the toxicity profile of off-label lenvatinib treatment in all adults advanced ATC patients, in France. Of the 23 patients analysed (14 males; mean age 64 years), 15 were pure ATC and 8 were mixed tumors (i.e. with a differentiated or poorly differentiated component). Prior treatments i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…To our knowledge, no trials have looked at mTOR inhibitors in the context of ATC with mutation in the PI3K/AKT/mTOR pathway. Antiangiogenic treatments such as lenvatinib [ 132 ], a multikinase inhibitor approved in differentiated thyroid cancers, have shown initially encouraging results but limited activity in subsequent studies, with a risk of bleeding and fistula as this disease often invades the trachea, esophagus and vessels, and are thus not recommended [ 2 , 77 , 133 ]. A recent prospective phase II trial was halted for futility as the minimum ORR threshold of 15% was not met upon interim analysis with a 2.9% response rate, a median PFS of 2.6 months and a median OS of 3.2 months [ 134 ].…”
Section: Treatment: To Treat Aggressively or To Palliate The Symptoms?mentioning
confidence: 99%
“…To our knowledge, no trials have looked at mTOR inhibitors in the context of ATC with mutation in the PI3K/AKT/mTOR pathway. Antiangiogenic treatments such as lenvatinib [ 132 ], a multikinase inhibitor approved in differentiated thyroid cancers, have shown initially encouraging results but limited activity in subsequent studies, with a risk of bleeding and fistula as this disease often invades the trachea, esophagus and vessels, and are thus not recommended [ 2 , 77 , 133 ]. A recent prospective phase II trial was halted for futility as the minimum ORR threshold of 15% was not met upon interim analysis with a 2.9% response rate, a median PFS of 2.6 months and a median OS of 3.2 months [ 134 ].…”
Section: Treatment: To Treat Aggressively or To Palliate The Symptoms?mentioning
confidence: 99%
“…We initially identified 349 studies. Finally, our study included 10 studies, namely, 2 prospective studies (13,18) and 8 retrospective studies (19)(20)(21)(22)(23)(24)(25)(26) (Figure 1). The characteristics of the study are shown in Table 1.…”
Section: Search Results and Study Quality Assessmentmentioning
confidence: 99%
“…Two single-arm studies (13, 18) scored 12 points using the MINORS index, which were acceptable for the current metaanalysis. Eight retrospective studies (19)(20)(21)(22)(23)(24)(25)(26) were evaluated using the JBI Critical Appraisal Checklist for Case Series (Table 2).…”
Section: Search Results and Study Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last decade, it has been emerging that ATC is a heterogeneous disease and that a more personalized approach could improve the patient prognosis. In this context, a recent French study showed that, among ATC patients treated with lenvatinib, the long-term survivors had a mixed histology of ATC combined with a more differentiated component [ 7 ]. Paucicellular ATC is an infrequent variant of ATC, which was associated with a better (although still poor) prognosis than classical ATC [ 8 ].…”
Section: Introductionmentioning
confidence: 99%